Paper Production In The Kokand Khanate: Historical Stages Of Development And Social Significance - Begmatov Khurshid Isanaliyevich (International Journal Of History And Political Sciences, 2025)
This study investigates the historical development and socio-cultural significance of paper production within the Kokand Khanate, focusing on the operation of paper-making workshops in Kokand and its surrounding regions. The research outlines the key stages in the evolution of local paper craftsmanship and examines the economic role of paper as a valuable commodity in both internal markets and international trade networks of the khanate. Drawing on historical sources and scholarly interpretations, the article analyses traditional technologies used in producing Kokand paper, identifies characteristic features of its main varieties, and compares them with the well-established paper-making techniques of China and the renowned Samarqand paper tradition. The findings contribute to a deeper understanding of Central Asian craft heritage and highlight the importance of Kokand’s paper industry in the cultural and economic landscape of the region.